2016
DOI: 10.1038/srep34730
|View full text |Cite
|
Sign up to set email alerts
|

Novel population of small tumour-initiating stem cells in the ovaries of women with borderline ovarian cancer

Abstract: Small stem cells with diameters of up to 5 μm previously isolated from adult human ovaries indicated pluripotency and germinal lineage, especially primordial germ cells, and developed into primitive oocyte-like cells in vitro. Here, we show that a comparable population of small stem cells can be found in the ovarian tissue of women with borderline ovarian cancer, which, in contrast to small stem cells in “healthy” ovaries, formed spontaneous tumour-like structures and expressed some markers related to pluripot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 69 publications
(89 reference statements)
3
47
0
Order By: Relevance
“…Cisplatin or its derivative used as first line therapeutics do not target CSCs, which undergo amplification and result in recurrences of cancer. Ovarian tumor contains various population of cancer stem cells [ 17 - 19 ]. ALDH1 positive CSCs is a major population and its expression has been related to tumor progression and metastasis [ 19 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cisplatin or its derivative used as first line therapeutics do not target CSCs, which undergo amplification and result in recurrences of cancer. Ovarian tumor contains various population of cancer stem cells [ 17 - 19 ]. ALDH1 positive CSCs is a major population and its expression has been related to tumor progression and metastasis [ 19 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALDH enzyme family contains 19 enzymes that are present in all cellular compartments, where they catalyze NADP + dependent oxidation of various aldehydes. Despite 19 isoforms of ALDH and each isoform having its own specific function, ALDH1 is the most often correlated with cancer stem cells and is found in various tissues [ 17 ]. In epithelial ovarian cancer, some investigators suggested the usefulness of ALDH1 activity to identify CSC population.…”
Section: Introductionmentioning
confidence: 99%
“…Age-dependent compromised function of niche supporting the stem cells results in menopause and can be manipulated to regenerate the non-functional ovary from VSELs 39 . VSELs have also been reported in large numbers in human ovarian tumour tissue 45 and mice studies 46 suggest that these may be responsible for formation of leiomyoma that arise from uterine myometrium. ( ix ) FSHR are expressed on VSELs/HSCs/SSCs/OSCs in addition to Sertoli cells in testis and granulosa cells in the ovary.…”
Section: Do Stem Cells Initiate Cancer?mentioning
confidence: 99%
“…VSELs in ovary surface epithelium are best candidates that could undergo malignant transformation into CSCs [73]. The small sized CSCs in ovarian cancers divided rapidly and spontaneously formed tumorlike structures in vitro as well as in vivo [74].…”
Section: Gonadal Stem Cells and Germ Cell Tumorsmentioning
confidence: 99%